26‐2: Extremely High‐Efficient OLED Achieving External Quantum Efficiency over 40% by Carrier Injection Layer with Super‐Low Refractive Index. Issue 1 (30th May 2018) - Watabe, Takeyoshi; Yamaoka, Ryohei; Ohsawa, Nobuharu; Tomida, Airi; Seo, Satoshi; Yamazaki, Shunpei
Abstract : Extremely low‐refractive‐index hole‐injection and electron‐injection layers were developed to improve the outcoupling efficiency of an organic light‐emitting diode (OLED). These layers enabled a remarkably high external quantum efficiency of 41% in a bottom‐emission phosphorescent OLED and also improved the current efficiency even in a top‐emission OLED with a microcavity structure.